Hertzian, Disruptive, Experimental Text Physicalizations - Koutsomichalis, Marinos (My University, 2019)
A series of creative text physicalizations are accounted for herein, with reference to research literature and, most importantly, to an experimental algorithmic system designed and implemented by the author. The latter concerns a series of experimental pipelines that ‘understand’ the input text generating keywords, that utilize them to query 3D data from WWW, and, finally, that transfigure and merge the latter so that new original artefacts are synthesized. The various physical, digital, and post-digital material affordancies of the resulting physicaliza- tions are scrutinized in some depth and in an analytic fashion. Objects of sorts are shown to be ascribed a certain kind of emergent neo-materiality, in that they are themselves hybrid manifestations of interwoven physical and digital affairs. As such, they constitute situated inquiries of the very same (technological) paradigms that brought them forth, as well as of their cultural and ideological offshoots. Physicalizations of sorts are shown to be ‘Herzian’, post-optimal, and disruptive, being both the creative means towards an exploration of new kinds of materiality/objecthood, and an implicit critique of the canonical functional design schemata that largely pertain digital fabrication nowadays.
Keywords: Physicalization; Post-digital; 3D printing; Solid modeling; Digital fabrication; Natural Language Understanding; 3D Data